Agente virtual para brindar asistencia acerca del covid-19 - Carrión Ojeda, José Alexis (2022)
In Ecuador, the health emergency caused by COVID-19 caused collapses in hospital centers, specifically in Loja city, severe cases were treated during the quarantine period established by the Ecuadorian state and resulted in minor cases not having access to public medical care, which affected a large number of people who could not afford a private professional, faced with this problem, the main objective of this Degree Project (TT) is to provide assistance about Covid-19 through a conversational agent (chatbot) to support the health sector in resolving common issues that people have without the need to consult other external sources that promote misinformation. The phases of the Desing Thinking methodology were used. The Knowledge Discovery in Text (KDT) methodology was used in the creation of the model, since the answers were obtained from documents extracted from a database, which were processed in the Python language, thanks to libraries such as HuggingFace Transformers to tokenize the texts, Pytorch to execute and adjust the BERT model, Haystack to extract the related context from the searches, JSON to store and manipulate the information, Googletrans to translate the information, the interface design was developed in Streamlit for the interaction of the users with the agent and the lifting of services through containers in Azure and Google Cloud. The information was extracted from scientific articles using the pre-trained BERT model in the SQuAD 2.0 dataset to adjust the model (fine-tune), the performance of the model was evaluated with the score or score produced in each of the answers, obtaining an optimized model in topics related to Covid-19. It was concluded that a functional virtual agent can be designed with the use of the BERT model together with SQuAD, since the evaluation carried out by health professionals corroborated that the responses provided by the agent were appropriate. Keywords: Covid-19, virtual agent, chatbot, BERT, SQuAD, transformers.